SOSIALISASI PENCEGAHAN PENYEBARAN COVID-19 DI KABUPATEN MUNA BARAT TAHUN 2020 - La Ode Nggawu; Siam Siam; Wa Ode Fatmawati; Alimin Alimin (Universitas Halu Oleo, 2021)
In Indonesia, since the first two cases of COVID-19 announced on March 2, 2020, the number of cases has continued to increase in 32 provinces. Seeing this situation, the acceleration of COVID-19 snacks must be carried out thoroughly and involve all parties including universities. This community service aims to support and strengthen the Covid-19 prevention and prevention program carried out by the Central Government and Regional Governments. This service is done in the form of online education through social media namely Facebook, WhatsApp, and Instagram. Also, to support online socialization, activities were carried out on distributing masks, installing banners, and leaflets about preventing the spread of Covid-19 and making handwashing (Westafel portable). Online socialization activities are carried out by creating a WhatsApp group as a media to disseminate information related to preventing the spread of Covid-19; mask distribution is done by delivering directly to the residents' houses to prevent the crowd; pamphlets are installed in public places such as markets, village halls, places of worship and schools; making washing places for hands in public places and places of worship; and banners in several districts of Tiworo Raya, Lawa Raya, and Kusambi Raya. With the Covid-19 Prevention socialization conducted by the UHO Thematic KKN team in West Muna, it was very helpful in raising public awareness to avoid Covid-19.